INTERACTIVE FORMS AND METHODS IN THE APPLICATION OF FOREIGN LANGUAGE TEACHING: https://doi.org/10.5281/zenodo.15364313 - Matkarimova, D.A. (International scientific and practical conference, 2025)
The article examines the implementation of interactive methods and forms in foreign language teaching, which are highly relevant in the current educational context. It discusses various interactive approaches and provides practical guidelines for their integration into the educational process. Additionally, the article includes an excerpt from a lesson that utilizes these methods.